The Effect of Music Therapy on Preoperative Anxiety Levels of Patients at Hospital X - Kurniawati Kurniawati; Rezqiqah Aulia Rahmat (International Journal of Health Sciences, 2025)
Preoperative anxiety is a common psychological response experienced by patients before undergoing surgery. High levels of anxiety can negatively impact the patient's physiological stability and the success of the surgical procedure. One non-pharmacological intervention that can be used to reduce anxiety is music therapy. This study aims to determine the effect of music therapy on preoperative anxiety levels in patients at Hospital X. This study used a quasi -experimental design with a pre-test and post-test approach with a control group. The study sample consisted of 60 pre- operative patients divided into an intervention group (n=30) and a control group (n=30). Anxiety levels were measured using the Hamilton Anxiety Rating Scale (HARS). The intervention group received instrumental music therapy for 20–30 minutes before surgery, while the control group received only standard care. Data analysis was performed using paired t-tests and independent t-tests. The results showed a significant decrease in anxiety levels in the intervention group compared to the control group (p < 0.05). Music therapy has been shown to be effective in reducing preoperative anxiety in patients . Therefore, music therapy can be recommended as a non-pharmacological nursing intervention in preoperative care.